Maintaining Indonesian Muslim Identity through Islamic Study Groups - Fakhruroji, Moch (Komunitas, 2019)
As a minority group in Australia, Indonesian Muslims are potentially experiencing identity crisis as they categorized as outsiders. This article describe how pengajian (Islamic study groups) and other socio-religious events among Indonesian Muslims as a constructive effort to change the perception of insiders over their social status in order to strengthen their identity as a member in a multicultural societies as theoretically, religion is believed to provide not only the meaning for life but also as social system which provides social control, cohesion, and purposes. Using the IMCV (Indonesian Muslim Community of Victoria) as a case, it could be identified that religious events can be a potential means to maintain their identity as Indonesian Muslims in the context of Australia